Small predators dominate fish predation in coral reef communities - Michalis Mihalitsis; Renato A. Morais; David R. Bellwood (PLoS Biology, 2022)
Ecosystem processes are challenging to quantify at a community level, particularly within complex ecosystems (e.g., rainforests, coral reefs). Predation is one of the most important types of species interactions, determining several ecosystem processes. However, while it is widely recognised, it is rarely quantified, especially in aquatic systems. To address these issues, we model predation on fish by fish, in a hyperdiverse coral reef community. We show that body sizes previously examined in fish–fish predation studies (based on a metanalysis), only represent about 5% of likely predation events. The average fish predator on coral reefs is just 3.65 cm; the average fish prey just 1.5 cm. These results call for a shift in the way we view fish predation and its ability to shape the species or functional composition of coral reef fish communities. Considered from a functional group approach, we found general agreement in the distribution of simulated and observed predation events, among both predator and prey functional groups. Predation on coral reefs is a process driven by small fish, most of which are neither seen nor quantified. When we think of fish predators on coral reefs we immediately think of sharks, groupers and barracudas. By modelling entire fish communities and comparing the results with published gut content data, this study reveals that the average fish-eating-fish predator on coral reefs is under 5 cm long; the vast majority of life and death events involve small fish being eaten by small predators.